(untitled) (Journal of Parents and Teachers, 2014)
Recently, the layout of roads and railways has been adapted to the topography of the terrain, but the application of new techniques has led to changes which have increased the impact they have on the environment. Students need to be able to assess the impact of such human activities on the environment. For this reason, this article presents a series of activities on environmental impact for students in the second year of E.S.O. (mandatory secondary education).